2013
DOI: 10.1039/c2nr32972g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–ferromagnet interfaces: hybridization, magnetization and charge transfer

Abstract: Electronic and magnetic properties of graphene-ferromagnet interfaces are investigated using first-principles electronic structure methods in which a single layer graphene is adsorbed on Ni(111) and Co(111) surfaces. Due to the symmetry matching and orbital overlap, the hybridization between graphene pπ and Ni (or Co) d(z(2)) states is very strong. This pd hybridization, which is both spin and k dependent, greatly affects the electronic and magnetic properties of the interface, resulting in a significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 38 publications
0
53
1
Order By: Relevance
“…Using Co and Ni interchangeably in this work is a good approximation as can be judged from detailed DFT calculations 19 . Nevertheless, there are some quantitative differences in the amount of charge transfer and the magnetic moment on the graphene mainly induced by slight changes in the bonding lengths both in the graphene and the interface layer involved.…”
Section: Discussionmentioning
confidence: 99%
“…Using Co and Ni interchangeably in this work is a good approximation as can be judged from detailed DFT calculations 19 . Nevertheless, there are some quantitative differences in the amount of charge transfer and the magnetic moment on the graphene mainly induced by slight changes in the bonding lengths both in the graphene and the interface layer involved.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to fabricate graphene-based spintronic devices as new potential materials for magnetic tunneling junction (MTJ) applications. The Ni(111) surface is the most commonly used metal contact to study graphene-based spintronics owing to its structure similar to that of graphene (the smallest lattice mismatch among other transition metals) and its strong hybridization with graphene [7,16]. Recent experimental and theoretical studies of graphene in a sandwich structure with Ni(111) suggested two structural models: (i)Ni/graphene/Ni contact, where graphene is used as a bridge between two nickel electrodes and the current flow is parallel to the plane, and (ii)Ni/Graphene/Ni spin valve structure, which consists of two Ni slabs sandwiching a graphene layer and the current flows out of the plane.…”
Section: Introductionsmentioning
confidence: 99%
“…There have been numerous experimental and theoretical studies on graphene contacted to metals such as Ni, Co, Ru, Rh, Pd, Ir, Pt and Cu. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Experimental studies about the growth of graphene on metal close-packed surface such as Ni(111), Cu(111) and Ru(0001) rank rst. [38][39][40][41] Secondly, experimental studies about the growth of graphene on other low-index metal surfaces such as Ni(100), Rh(100) and Pt(110) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] However, theoretical studies on the interfaces between graphene and metals mainly focus on the metal close-packed surface such as Ni(111), Co(111), Cu(111) and so on. [28][29][30][31][32][33][34][35][36][37] In 2018, Mafra et al not only investigated different growth mechanisms of graphene on Ni(100), (110) and (111) surface by optical microscopy, Raman spectroscopy and optical transmission but also provided an atomistic model of the processes involved to support the experimental results by density functional theory calculations. 43 Theoretical studies on the adsorption of graphene on the (110) and (100) surfaces of other metals except Ni are rarely reported.…”
Section: Introductionmentioning
confidence: 99%